ANALISIS FAKTOR MEREK, KEGUNAAN SITUS WEB DAN HARGA YANG MEMPENGARUHI PERSEPSI KONSUMEN TERHADAP AGEN PERJALANAN ONLINE - Nurhalim, Andres Dharma (Publika Citra Media, 2024)
The rapid development of information technology today has a significant effect on all human life and also makes business organizations easier to do business. Travel and tourism have illustrated how e-commerce can change the structure of the industry and in the process create new business opportunities. Although the online travel agent market is still small, it poses a threat to traditional/conventional travel agents because it operates 24 hours. However, travel companies can take advantage of opportunities by implementing e-commerce technology in their business. The purpose of this study was to identify whether brand, website usability, and price affect customer perceptions in choosing an online travel agent. The number of respondents participating in this study was 116 samples that could be taken using a random sampling method to Indonesian internet users who had made online transactions. This study uses multiple linear regression with the SPSS 21 statistical program. The results showed that the variables brand, website usability, and price have a positive effect partially and simultaneously on customer perceptions.